PENERAPAN MODEL PEMBELAJARAN PEMBANGKIT ARGUMEN PADA MATERI OPTIK UNTUK MENINGKATKAN KEMAMPUAN ARGUMENTASI SISWA KELAS VIII SMPN 20 PEKANBARU - Jayanti, Armila; M.Nor, M.Nor; Rahmad, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to determine the effect of Generate Argument Instruction model toward student argumentation skills on optical material. Quasy experiment was use as study model by using intact group comparison. The population in this study were students grade VIII of SMPN 20 Pekanbaru which consisted of seven classes. Two classes whas choosen to be experiment and control class based on normality and homogenity test. The data was analyze by using descriptive and inferential statistic techniques. The result of this study showed there was a sifnificant influence toward students argumentation skill between experiment class that using implementy Generate Argument Instructional Model and control class that using conventional learning. The argumentation skill of experimental class was higher than class control (12,7%). It can be conclude, the generate argument instructional model gave the positive effect toward student’s argumentation skills.Keywords : Generate argument instruction model, argumentation ability, optic